(untitled) (American Journal of Islam and Society, 2007)
I would like to thank AMSS, and specially Jamin Zine, for inviting me to address your conference on “Islam: Tradition and Modernity” today. Since I am in the midst of enjoying your splendid hospitality, I feel I should begin with an apology for what I am about to say. A polite guest would have praised the food and your conference and gone home without being critical of anything. But unfortunately for you, I was born with an impolitic gene and so I am going to take this opportunity to critique the way in which your conference is framed. The basic point I will make is a simple one: It is not very productive to study Islam through the lenses of tradition and modernity. This is not because one cannot say anything meaningful about Islam in those two contexts; rather, it is because binary modes of thinking are themselves problematic. I will make this point in two ways: first by critiquing the tradition vs. modernity binary and binaries in general and, second, by sharing my own work on Qur’anic hermeneutics as an example of how we might get beyond binaries. Whether my comments will serve to muddy the waters or to clarify them remains to be seen ...